2020
DOI: 10.31488/bjcr.153
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Liver Cancer Cell Response to Cryoablation and AdjunctiveBased Cryo Chemotherapy

Abstract: The incidence of liver cancer has more than tripled in the last 40 years. The American Cancer Society estimates 42,810 new cases will be diagnosed and 30,000 will die from liver cancer in 2020 in the US alone [1]. Current treatment depends on staging, with early stage tumors defined as potentially resectable. In cases where surgery is not possible due to tumor size, proximity to blood vessels, or other factors chemotherapy, targeted molecule therapy, and immunotherapy via systemic or intrahepatic infusion are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Similar positive outcomes have been reported by Petrone et al [38] and Kovach et al [38]. These, and other, reports demonstrate the potential for cryoablation to treat PaCa [28,39,40]. Given that some PaCa tumors are poor candidates for surgical resection due to proximity to blood vessels and other organs, the precise targeting of cancerous cells with cryoablation could expand therapeutic options to more patients.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar positive outcomes have been reported by Petrone et al [38] and Kovach et al [38]. These, and other, reports demonstrate the potential for cryoablation to treat PaCa [28,39,40]. Given that some PaCa tumors are poor candidates for surgical resection due to proximity to blood vessels and other organs, the precise targeting of cancerous cells with cryoablation could expand therapeutic options to more patients.…”
Section: Introductionsupporting
confidence: 76%
“…A recently completed clinical trial (NCT03695835) on the combination of cryoablation and pembrolizumab included a PaCa subgroup with initial results showing a benefit. We, as well as others, have published numerous studies on the effects of the combination of freezing with adjunctive agents, including chemotherapeutic drugs and nutraceuticals, in various cancer cell systems [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. The objective of this combinatorial adjunctive agent approach is to elevate the minimum lethal temperature necessary to fully ablate a tumor, thus ensuring complete cancer cell destruction with minimal over-freezing.…”
Section: Introductionmentioning
confidence: 99%
“…This prevented detailed histological characterization of the ablated tissue areas. Thirdly, while studies have shown that liver and pancreatic tissue have a similar minimal lethal temperature range (−20 °C to −25 °C) [ 26 , 68 , 70 , 71 , 91 ], extrapolation of the in vivo findings on liver tissue cryoablation to that of pancreatic tissue cryoablation using FrostBite should be with caution. To address these items, future in vivo studies will include expanded survival studies, histological analysis (H&E and trichrome staining), in vivo tumor models, and investigation of freeze duration (time and repeat freezes) on lesion size.…”
Section: Discussionmentioning
confidence: 99%
“…The lethal temperature varies between cancer and tissue types, necessitating careful planning and visualization (tumor and frozen mass) to achieve maximum targeted destruction while avoiding damage to adjacent structures [ 17 , 18 ]. For instance, studies have shown that for the destruction of pancreatic and renal cancer, a minimal lethal temperature (MLT) of <−25 °C must be attained, whereas for late-stage prostate cancer, temperatures <−40 °C are necessary [ 19 , 20 , 21 , 22 , 23 ]. Application of a double freeze (providing repeat thermal insult in a finite window) has been shown to increase the MLT in the range of 5 to 10 °C [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies have shown that for the destruction of pancreatic and renal cancer, a minimal lethal temperature (MLT) of <−25 °C must be attained, whereas for late-stage prostate cancer, temperatures <−40 °C are necessary [ 19 , 20 , 21 , 22 , 23 ]. Application of a double freeze (providing repeat thermal insult in a finite window) has been shown to increase the MLT in the range of 5 to 10 °C [ 19 , 20 , 21 , 22 , 23 ]. In the case of LC, while numerous studies have demonstrated that CA can be used to effectively target NSCLC and support lethality in the −20 °C to −35 °C range [ 24 , 25 , 26 ], the definition of the MLT for LC remains unclear.…”
Section: Introductionmentioning
confidence: 99%